From Fragmentation to Collective Action: A System Dynamics–Based Approach to Addressing Stakeholder Engagement in the Building Sector’s Circular Economy Transition - Fuat Emre Kaya (Buildings)
The building sector holds significant potential to mitigate climate change by adopting the circular economy. However, its transition is impeded by fragmented stakeholder engagement arising from complex socio-organisational dynamics. To address this, this article adopted the system dynamics (SD) modelling tool, which enables structured visualisation of the system while exploring and assessing stakeholder dynamics. The three-stage methodological approach includes the following: problem identification, building on the author’s prior publication, which identified the variables and their direct relationships; system conceptualisation, where the causal loop diagram was developed, followed by the identification of feedback loops, construction of the stock-flow diagram, and ultimately the SD model to capture indirect relationships; and model optimisation, which calibrated the SD model based on real-world circular building scenarios. The results revealed the stakeholder dynamics through their associated concerns. The results indicated that leveraging stakeholder dynamics within the complex system could foster collective action from fragmentation to enable the effective circular economy transition. This article proposes general and phase-specific actions tailored to each stakeholder, offering a structured framework for coordinated decision-making. These actions help bridge the gap between theory and practice, facilitating the sector’s transition from its current linear model toward a more collaborative and circular approach to climate change mitigation.